The impact of coping strategies, test anxiety and expectancies on the University entrance trial exam scores - Önen, Pınar. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
This study explored the relationship between test anxiety, trait anxiety, coping strategies and the University Entrance Exam (UEE) related variables (perceived importance of the UEE, achievement expectation of self, perceived achievement expectation of mother, father and teacher, trial exam performance). The sample consisted of 227 students who were preparing for the University Entrance Examination. Lazarus and Folkman's Ways of Coping Scale was used to assess students' coping strategies in dealing with the UEE stress. Results indicated that trait anxiety and test anxiety had no relationship with trial exam score. On the other hand, students who used adaptive coping strategies; i.e. problem-focused coping, support seeking, positive reappraisal and emotional expression coping strategies had higher trial exam scores. Furthermore, achievement expectancy and importance of UEE were both correlated with anxiety, coping strategies and academic performance of the students. Findings pointed out that, coping strategies used by the students were found to be both affected by dispositional characteristics and situation specific responses of the students.
Keywords: Test anxiety.; Educational tests and measurements.